Eye-Tracking Metrics in Software Engineering - Sharafi, Zohreh; Shaffer, Timothy; Sharif, Bonita; Gueheneuc, Yann-Gael (Proceedings / Asia Pacific Software Engineering Conference, 2015)
Eye-tracking studies are getting more prevalent in software engineering. Researchers often use different metrics when publishing their results in eye-tracking studies. Even when the same metrics are used, they are given different names, causing difficulties in comparing studies. To encourage replications and facilitate advancing the state of the art, it is important that the metrics used by researchers be clearly and consistently defined in the literature. There is therefore a need for a survey of eye-tracking metrics to support the (future) goal of standardizing eye-tracking metrics. This paper seeks to bring awareness to the use of different metrics along with practical suggestions on using them. It compares and contrasts various eye-tracking metrics used in software engineering. It also provides definitions for common metrics and discusses some metrics that the software engineering community might borrow from other fields.